An overview on development of broiler breeding research in India - Khan, A G (The Indian Journal of Animal Sciences, 2012)
Broiler breeding research in India is organized in private and public sectors. In private sector international breeding organizations are collaborators with Indian counter parts, whereas public sector is supported by the Indian Council of Agricultural Research, New Delhi. Private sector data on pure line development in India is scarcely available. From public sector Project Directorate on Poultry 4-line strains Pb1, Pb2, IC3 and IR3 are considered in the present review. Polygenic domain of genetic variability is extended to genome analysis through knowledge of sequenced DNA in terms of restricted fragment length polymorphism (RFLPS) which permitted genotype assisted selection. Closely linked microsetallite DNA are used to identify variability associated with target gene. About 662 such sequenced DNA RFLFS have been identified. Data analysis of growth selection studies for a decade revealed 20.5 to 40.0 g annual genetic gain in pure bred broiler population with realized heritabilities of 0.20 to 0.22. The regression analysis showed decline in genetic variance with advance in generation number. Correlated responses for egg number was negative in male line but female line did show 1 egg increase per year, with decline of 1.5 days in age of marketing. Studies on feather color chromatism, comb pattern, feed efficiency traits, lean carcass selection and major gene like dwarf and naked neck are under progress. Indian bred commercial broiler weighed 1.4 to 1.5 kg at 6 weeks of age which is about 10-12% less than those from private sector.